ANALISIS IMPLEMENTASI TALENT MANAGEMENT DALAM MENGEMBANGKAN KINERJA KARYAWAN YANG UNGGUL DAN BERBUDAYA - Putu Dharmawan Pradhana; I Made Bima Devrasta Putra Astaki; I Dewa Ketut Gede Prabawa (GoAcademica Research dan Publishing, 2021)
Human Resources (HR) it is a determining factor for the effectiveness of activities within the organization. A person's success and performance in a field of work is largely determined by the level of competence, professional performance and commitment to the field of work he is engaged in. Quality human resources will have a positive effect on the organization/company, both in terms of improving performance, effectiveness and efficiency in a company. Another thing that is no less important and must be a concern for an organization/company is how they develop their human resource potential. One way that can be done is through talent management. This talent management can be applied by various institutions, both government agencies, private sector and local companies. Likewise, employees at the Regional Public Company for Drinking Water Tirta Mangutama, Badung Regency. The approach in this research is qualitative research. The data sources used consist of primary data and secondary data. Data collection techniques in this study by observation, interviews, and documentation. In determining the informants used purposive sampling technique. The technique of checking the validity of the data used the source triangulation technique and the triangulation technique, as well as the data analysis technique using the Miles and Huberman technique, namely interactive model analysis. The expected result in this research is the implementation of Talent Management in the process of developing superior and cultured employee performance at the Regional Public Company for Drinking Water Tirta Mangutama, Badung Regency.